2018
DOI: 10.1002/jcp.27411
|View full text |Cite
|
Sign up to set email alerts
|

Cyclooxygenase‐2 in cancer: A review

Abstract: Cyclooxygenase-2 (COX-2) is frequently expressed in many types of cancers exerting a pleiotropic and multifaceted role in genesis or promotion of carcinogenesis and cancer cell resistance to chemo-and radiotherapy. COX-2 is released by cancerassociated fibroblasts (CAFs), macrophage type 2 (M2) cells, and cancer cells to the tumor microenvironment (TME). COX-2 induces cancer stem cell (CSC)-like activity, and promotes apoptotic resistance, proliferation, angiogenesis, inflammation, invasion, and metastasis of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
399
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 566 publications
(453 citation statements)
references
References 174 publications
3
399
1
2
Order By: Relevance
“…This inflammatory response is also mediated by the regulation of proinflammatory cytokines, such as IL‐1β, TNFα, and by the activation of transcription factors, such as NF‐κB). ISP‐VT significantly reduced COX‐2 expression in the subplantar tissue of mice in the count of positively labeled cells for this enzyme when compared to the group treated with carrageenan (Hashemi Goradel, Najafi, Salehi, Farhood, & Mortezaee, ; Wallace & Vong, ; Yu, Lao, & Zheng, ). Our results showed that one of the mechanisms of the anti‐inflammatory activity of ISP‐VT is COX‐2 inhibition.…”
Section: Resultsmentioning
confidence: 95%
“…This inflammatory response is also mediated by the regulation of proinflammatory cytokines, such as IL‐1β, TNFα, and by the activation of transcription factors, such as NF‐κB). ISP‐VT significantly reduced COX‐2 expression in the subplantar tissue of mice in the count of positively labeled cells for this enzyme when compared to the group treated with carrageenan (Hashemi Goradel, Najafi, Salehi, Farhood, & Mortezaee, ; Wallace & Vong, ; Yu, Lao, & Zheng, ). Our results showed that one of the mechanisms of the anti‐inflammatory activity of ISP‐VT is COX‐2 inhibition.…”
Section: Resultsmentioning
confidence: 95%
“…Cyclooxygenases (COXs) are cytoplasmic enzymes that catalyze the rate-limiting step of prostaglandin biosynthesis in mediator participating in several biological processes. COX-2 is known to inhibit apoptosis and induce proliferation patterns such as, angiogenesis, inflammation, invasion, and metastasis of cancer cells (Stasinopoulos et al, 2013), (Hashemi Goradel et al, 2019). The present study assessed the suppression of miR-144 is able to markedly activate proliferation and modulate COX-2 expression in ovarian cancer cells.…”
Section: Discussionmentioning
confidence: 92%
“…High COX‐2 expression is thought to play an important role in tumorigenesis through various mechanisms modulated by increased production of prostaglandins: stimulation of cell proliferation, inhibition of apoptosis, maintenance of cancer stem cell features, increasing of cell invasiveness, enhancement of angiogenesis and affect on immune system. In turn, the COX‐2 peroxidase activity may contribute to production of mutagens (Figure ) …”
Section: Cyclooxygenase‐2 In Cancermentioning
confidence: 99%
“…In turn, the COX-2 peroxidase activity may contribute to production of mutagens ( Figure 1). [5][6][7][8] Enhanced COX-2 expression was demonstrated in various types of human malignancies: carcinomas of colon, 9,10 breast, 11,12 lung, 13,14 stomach, 15,16 esophagus, 17,18 pancreas, 19 bladder, 20 prostate, 21 ovary, 22,23 cervix, 24,25 osteosarcomas, 26,27 gliomas, 28,29 and Hodgkin lymphomas. 30 In most of the studies, it was shown that cancer progression is accompanied by an increase in COX-2 levels and may have prognostic potential.…”
Section: Cyclooxygenase-2 In Cancermentioning
confidence: 99%